2014
DOI: 10.1186/gb-2014-15-4-r55
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profile analysis of diffuse-type gastric cancers

Abstract: BackgroundStomach cancer is the third deadliest among all cancers worldwide. Although incidence of the intestinal-type gastric cancer has decreased, the incidence of diffuse-type is still increasing and its progression is notoriously aggressive. There is insufficient information on genome variations of diffuse-type gastric cancer because its cells are usually mixed with normal cells, and this low cellularity has made it difficult to analyze the genome.ResultsWe analyze whole genomes and corresponding exomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 72 publications
3
54
1
1
Order By: Relevance
“…The landmark study of GC molecular-based stratification was carried out by The Cancer Genome Atlas (TCGA) research network [54], which proposed a fourtiered molecular classification that identifies: (1) EpsteinBarr virus-positive (EBV+) GC, characterised by recurrent PIK3CA mutations, frequent JAK2 and PD-L1 amplification, and a high level of DNA hypermethylation, as previously reported [57]; (2) GC with microsatellite in-stability (MSI-high) characterised by DNA hypermethylation and MLH1 silencing; (3) genomically stable GC, associated with a diffuse morphology and recurrent CDH1 and RHOA events, as confirmed by previous studies [58][59][60]; and (4) GC with chromosomal instability (CIN), exhibiting intestinal morphology, a high number of TP53 mutations, and amplifications of tyrosine kinase receptors (TKR).…”
Section: Moving Towards Molecular Subtyping and Precision Medicinesupporting
confidence: 60%
“…The landmark study of GC molecular-based stratification was carried out by The Cancer Genome Atlas (TCGA) research network [54], which proposed a fourtiered molecular classification that identifies: (1) EpsteinBarr virus-positive (EBV+) GC, characterised by recurrent PIK3CA mutations, frequent JAK2 and PD-L1 amplification, and a high level of DNA hypermethylation, as previously reported [57]; (2) GC with microsatellite in-stability (MSI-high) characterised by DNA hypermethylation and MLH1 silencing; (3) genomically stable GC, associated with a diffuse morphology and recurrent CDH1 and RHOA events, as confirmed by previous studies [58][59][60]; and (4) GC with chromosomal instability (CIN), exhibiting intestinal morphology, a high number of TP53 mutations, and amplifications of tyrosine kinase receptors (TKR).…”
Section: Moving Towards Molecular Subtyping and Precision Medicinesupporting
confidence: 60%
“…However, in this case, the underlying family predisposing gene was CTNNA1 and not CDH1 [39], and somatic mutations at LMTK3, MCTP2, MED12, PIK3CA, and ARID1A genes have been demonstrated, as well as mutations in other genes recently shown to be part of the molecular signatures of sporadic GC [54][55][56][57][58][59]. Similar studies in a series of HDGC caused either by CDH1 or CTNNA1 germline mutations, and in different progression stages, would undoubtedly help to disclose the somatic mutation landscape of this disease.…”
Section: Other Somatic Changes In Hdgcmentioning
confidence: 99%
“…28) or CDH1 (ref. 29) genes have been reported in hereditary diffuseGCs, and frequent PIK3CA mutations were observed in diffuse-type sporadic GCs 7 . On the basis of recent whole-genome and sequencing results on diffuse-type GCs, high mutation rates of CDH1, CTNNA1 or PIK3CA may specifically contribute to the carcinogenesis of diffuse-type GCs.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, stroma-dominant growth pattern and subsequent small cancer cell population within tumour has so far restricted application of large-scale next-generation sequencing studies on diffuse-type GC 3 . Recent comprehensive molecular characterization of GC proposed a molecular classification dividing GC into four subtypes 5 , and large-scale genomic studies reported gain-of-function mutations of RHOA in 0-25.3% of diffuse-type GCs [5][6][7][8] . However, some of those were performed with relatively low coverages (B6.19X (ref.…”
mentioning
confidence: 99%